Numerical Study on Thermodynamic Performance of a Novel Thermoacoustically Driven Refrigerator---Double-acting Traveling-wave Thermoacoustic Refrigerator - Yang Zhuo; Luo Ercang; Chen Yanyan (Zhileng xuebao)
A new thermoacoustic refrigerator which is driven by a double-acting traveling-wave thermoacoustic engine have been researched and designed. Through numerical simulation, we optimize the structure parameters of the refrigerator. Under the design conditions, the new refrigerator reaches a COP of 2.74, a relative Carnot efficiency of 60%, a consumed P-V power of 534W, and a cooling capacity of 1464.9W. In addition, a traditional Stirling refrigerator and the new thermoacoustic refrigerator with double-action operation are calculated and compared for operating pressure ratio, efficiency, cooling capacity and other features, and the simulated results show that the new thermoacoustic refrigerator is very efficient and suitable for coupling with a double-action, traveling-wave thermoacoustic engine. Thermoacoustic refrigerator with double-action operation has good potential as an alternative of ordinary refrigeration technology due to intrinsic high efficiency heat driven mechanism, no moving components and environmental friendliness, etc.